Stable Stratification of the Helium Rain Layer Yields Vastly Different Interiors and Magnetic Fields for Jupiter and Saturn - S. Markham; T. Guillot (The Planetary Science Journal)
At sufficiently high pressures (∼Mbar) and low temperatures (∼10 ^3 –10 ^4 K), hydrogen and helium become partly immiscible. Interpretations of Jupiter’s and Saturn’s magnetic fields favor the existence of a statically stable layer near the Mbar pressure level. From experimental and computational data for the hydrogen–helium phase diagram, we find that moist convection and diffusive convection are inhibited, implying a stable helium rain layer in both Jupiter and Saturn. However, we find a significant difference in terms of structure and evolution: in Jupiter, helium settling leads to a stable yet superadiabatic temperature gradient that is limited by conductive heat transport. The phase separation region should extend only a few tens of kilometers, instead of thousands in current-day models, and be characterized by a sharp increase of the temperature of about 500 K for standard phase separation diagrams. In Saturn, helium rains occur much deeper, implying a larger helium flux relative to planetary mass. We find that the significant latent heat associated with helium condensation implies that a large fraction, perhaps close to 100%, of the planet’s intrinsic heat flux may be locally transported by the sinking helium droplets. This implies that Saturn may possess a much more extended helium rain region. This also accounts, at least qualitatively, for the differences in strength and characteristics of the magnetic fields of the two planets. Dedicated models of magnetic field generation in both planets may offer observational constraints to further refine these findings.